The Last World Financial Crisis and its Consequences - García-Osorio, Nelson (2015)
The global crisis has its origin in the "heart" of the 2007 US financial system. Reliance on low-quality mortgage securities lost, the asset prices down, reducing liquidity and uncertainty in financial markets generated a progressive impact on economic activity through international trade channels is reduced aggregate demand worldwide, marking the recessive dynamics.